METHODOLOGY OF USING EDUCATIONAL GAMES IN THE LESSON PROCESS IN GENERAL SECONDARY SCHOOLS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The use of educational games in the classroom in general secondary schools makes the learning process of students more interesting, effective and active. Today, pedagogical experiments show the importance of educational games in developing such skills as logical thinking, creative approach, independent thinking, teamwork in students. This article analyzes the methodology for using educational games in the classroom, their impact on educational effectiveness, types of games and the possibilities of increasing student motivation through them. Proper organization of educational games plays an important role in increasing students' interest in the lesson and consolidating knowledge. The article also provides recommendations for teachers on the effective use of educational games and gives practical examples.